2013
DOI: 10.1186/1471-2393-13-161
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of placental growth factor and fetal flow Doppler ultrasonography to identify fetal adverse outcomes in women with hypertensive disorders of pregnancy: an observational study

Abstract: BackgroundHypertensive disorders of pregnancy and intrauterine growth restriction (IUGR) are leading causes of maternal and perinatal morbidity and mortality. Failure to detect intrauterine growth restriction in women at high risk has been highlighted as a significant avoidable cause of serious fetal outcome. In this observational study we compare fetal flow using Doppler ultrasonography with a new test for placental growth factor (PlGF) to predict fetal adverse events.MethodsEighty-nine women with hypertensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
(18 reference statements)
0
17
1
Order By: Relevance
“…Furthermore, it could be argued that the collapse of fetal circulation on its own is a primary reason for a reduction in PlGF levels. Although we cannot exclude this possibility, previous studies have found an inverse correlation between PlGF and fetal well-being in pregnancies in which fetal circulation was preserved [36]. Finally, in light of the sensitive situation of the women participating in this study, we recruited the minimal number of women that still allows valid statistical analysis.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, it could be argued that the collapse of fetal circulation on its own is a primary reason for a reduction in PlGF levels. Although we cannot exclude this possibility, previous studies have found an inverse correlation between PlGF and fetal well-being in pregnancies in which fetal circulation was preserved [36]. Finally, in light of the sensitive situation of the women participating in this study, we recruited the minimal number of women that still allows valid statistical analysis.…”
Section: Discussionmentioning
confidence: 96%
“…In humans, maternal plasma PGF deficiency is linked to the hypertensive disorder preeclampsia and fetal growth restriction [21][22][23]. However, neither the effects of PGF on regulation of maternal blood pressure nor the roles of PGF in fetal development and growth are known.…”
Section: Discussionmentioning
confidence: 97%
“…One major challenge is the increased risk of preeclampsia, eclampsia [6, 7], and related conditions, such as preterm delivery [5, 6] and intrauterine growth restriction [6, 8], that increase morbidity and mortality in the mother [2] and foetus [4, 9]. …”
Section: Introductionmentioning
confidence: 99%